Comparing the Effectiveness of Metacognitive Therapy and Compassion-Focused Therapy on Repetitive Thinking in Female Students with Non-Clinical Depression - Zare Zari Mahaleh, Marziyeh; Dousti, Yar Ali; Khosravi, Saeid Ahmad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to compare the effectiveness of Metacognitive Therapy (MCT) and Compassion-Focused Therapy (CFT) in reducing repetitive thinking among female university students with non-clinical depression and to identify the more effective intervention. Methods and Materials: This quasi-experimental study employed a pretest–posttest control group design with a three-month follow-up assessment. The statistical population consisted of female students with non-clinical depression at Islamic Azad University, Sari Branch, during the 2025 academic year. Forty-five participants were selected through purposive sampling and assigned to three groups: Metacognitive Therapy (n=15), Compassion-Focused Therapy (n=15), and a control group (n=15). Participants in the intervention groups received eight 90-minute sessions based on Wells’ Metacognitive Therapy protocol and Gilbert’s Compassion-Focused Therapy protocol, respectively. Data were collected using the Repetitive Negative Thinking Scale and analyzed through repeated-measures ANOVA, Bonferroni post hoc tests, and Tukey comparisons. Findings: Repeated-measures ANOVA demonstrated significant main effects for group (F=25.519, p<0.01, η²=0.549) and time (F=50.583, p<0.01, η²=0.546), as well as a significant group-by-time interaction effect (F=14.483, p<0.01, η²=0.408). Bonferroni analyses revealed significant reductions in repetitive thinking from pretest to posttest and follow-up (p<0.001), whereas the difference between posttest and follow-up was not significant, indicating maintenance of treatment gains. Tukey comparisons further showed that Metacognitive Therapy produced significantly greater reductions in repetitive thinking than Compassion-Focused Therapy (p<0.01). Conclusion: Both therapeutic approaches effectively reduced repetitive thinking among female students with non-clinical depression; however, Metacognitive Therapy demonstrated superior effectiveness. The findings suggest that directly modifying maladaptive metacognitive beliefs and cognitive processing styles may be more beneficial than compassion-based interventions for reducing repetitive thinking and preventing progression toward clinical depression.